Unlocking the Power of Online Assessments in EFL Education: Teachers’ and Students’ Perceptions - Ali Abbas Falah Alzubi; Mohd Nazim (SAGE Open)
In online learning, many teachers have adopted traditional assessment methods in offline assessments without adequately testing and assessing the consequences. Therefore, this descriptive study aims to identify teachers’ and students’ perceptions of online assessments in evaluating English as a Foreign Language (EFL) students’ learning. A convenient sample of teachers and students was recruited to respond to a questionnaire on their beliefs about and reported use of online assessment methods through management learning systems. Additionally, semi-structured interviews were conducted to explore participants’ experiences with online assessment. The results demonstrated that teachers’ and students’ beliefs regarding online assessments for EFL learning were moderate, indicating a shared but cautious acceptance of these methods. The analysis revealed no significant differences in perceptions based on participants’ roles, suggesting a common understanding of the challenges and benefits of online assessments among educators and learners alike. Qualitative responses highlighted six key themes: the nature of online assessments, time and effort required, performance outcomes, psychological pressure experienced, and overall user experience, reflecting the concerns regarding technological readiness, academic integrity, and the need for more diverse assessment methods. To enhance the effectiveness of online assessments in the EFL context, the study recommends ensuring a robust technological infrastructure, offering comprehensive training for teachers on various online assessment methods, diversifying assessment techniques to capture a broader range of student abilities, and fostering a culture of ethical assessment practices through close monitoring of student work.